Tingkat Aktivitas Fisik berhubungan dengan Derajat Tekanan Darah Pada Pasien Hipertensi - Aryanti, Khofifah; Pardede, Lisbeth (Jurnal Keperawatan Widya Gantari Indonesia, 2023)
Hypertension is blood pressure that exceeds normal limits in which there are disturbances in systolic > 140 mmHg and diastolic > 90 mmHg when repeated examinations are carried out. Hypertension is a non-communicable disease that still occurs a lot and is a degenerative disease and has a fairly high mortality rate. Handling hypertension so that blood pressure decreases such as doing physical activity. Physical activity can be done anywhere to fill spare time. The research aims to analyze the relationship betweenrelationship between the level of physical activity and blood pressure levels among hypertensive patients at UPTD Puskesmas Bintara Kota Bekasi. The research method employs a descriptive correlational design with a cross-sectional approach. Sampling with probability sampling technique and there are 99 respondents. The research results indicate that the majority of respondents have moderate physical activity levels, comprising 70 respondents (70.7%), and their blood pressure falls into the normal category, with 52 respondents (52.5%). The chi-square test yielded a p-value=0,0001. The conclusion is that there is a significant relationship between the level of physical activity and the degree of blood pressure in hypertensive patients at the UPTD Puskesmas Bintara, Bekasi City. Keywords: physical activity, blood pressure, hypertension